Triazine herbicides and ovarian epithelial neoplasms. - Donna, A; Crosignani, P; Robutti, F; Betta, P G; Bocca, R; Mariani, N; Ferrario, F; Fissi, R; Berrino, F (Scandinavian Journal of Work, Environment & Health, 1989)
The possible role of a class of herbicides, triazines, in ovarian carcinogenesis has been evaluated in a population-based case-referent study. The trade names reported by the study subjects, and the type of cultivation in which they worked, were used for the assessment of exposure. Women previously exposed to triazines showed a significant relative risk of 2.7 for ovarian neoplasms. Although none of the doses could be quantified for the study subjects, two risk trends in favor of the plausibility of the association were found: the first by duration and the second by probability of exposure. The population representativity of the study and the comparability of information between the cases and referents suggest the lack of any major bias in the results. Triazine-related risk remained consistent when the analysis was restricted to farmers and when the exposure to other herbicides and to other types of cultivation were considered. Unexposed farmers had the same risk as unexposed nonfarmers.